(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
For solid fuels ash melting temperature is recommended to be higher than 1000°C, so that it can be used in automated furnaces; therefore-promising energy crops are investigated as renewable energy source. This paper presents the results of tests on melting temperature of different energy crop ashes.The field trial was carried out in the study farm of the Latvia University of Agriculture "Pēterlauki" (56°53'N, 23°71'E) in the sod calcareous soils characterized by pH KCl 6.7, P 52 mg kg-1, K 128 mg kg-1, organic matter content from 21 to 25 g kg-1 in the soil. Energy crops analysed: reed canary grass (Phalaris arundinacea L.), birch (Betula pendula Roth.), osier (Salix spp.), grey alder (Alnus incana (L.) Moench), poplar (Populus tremula L.), hybrid aspen (Populus tremuloides x Populus tremula). Results indicate that the ash melting temperature (D, St, Ht, Ft) for the wood energy crops were higher than for the studied grass energy crops and their mixture. Ash melting temperature in all phases over 1200°C was observed for such poplar and hybrid aspen mixture proportions: 3 parts of wood and 1 part of reed canary grass, or 1 part of wood and 1 part of reed canary grass.